Amazonian Kichwa of the Curaray River : kinship and history in the Western Amazon - Reeve, Mary-Elizabeth (University of Nebraska Press, 2022)
"Amazonian Kichwa of the Curaray River is an exploration of the dynamics of regional societies and the ways in which kinship relationships define the scale of these societies. It details social relations across Kichwa-speaking indigenous communities and among neighboring members of other ethnolinguistic groups to explore the multiple ways in which the regional society is conceptualized among Amazonian Kichwa. Drawing on recent studies in kinship, landscape from an indigenous perspective, and social scaling, Mary-Elizabeth Reeve presents a view of Amazonian Kichwa as embedded in a multiethnic regional society of great historic depth. This book is a fine-grained ethnography of the Kichwa of the Curaray River region (Curaray Runa) in which Reeve focuses on ideas of social landscape, as well as residence, extended kin groups, historical memory, and collective ritual celebration, to show the many ways in which Curaray Runa express their placement within a regional society. The final chapter examines social scaling as it is currently unfolding in indigenous societies in Amazonian Ecuador through increasing multisited residence and political mobilization. Based on intensive fieldwork, Amazonian Kichwa of the Curaray River breaks new ground in Amazonian studies by focusing on extended kinship networks at a larger scale and by utilizing both ethnographic and archival research of Amazonian regional systems. "--